Different response of human chondrocytes from healthy looking areas and damaged regions to IL1β stimulation under different oxygen tension. Issue 1 (1st October 2018) - Huang, Xiaobin; Zhong, Leilei; Hendriks, Jan; Post, Janine N.; Karperien, Marcel
ABSTRACT: Due to its avascular nature, articular cartilage is relatively hypoxic. The aim of this study was to elucidate the functional changes of macroscopically healthy looking areas chondrocytes (MHC) and macroscopically damaged regions chondrocytes (MDC) at a cellular level in response to the inflammatory cytokine IL1β under different oxygen tension levels. In this study, two‐dimensional (2‐D) expanded MHC and MDC were redifferentiated in 3‐D pellet cultures in chondrogenic differentiation medium, supplemented with or without IL1β at conventional culture (normoxia) or 2.5% O2 (hypoxia) for 3 weeks. qPCR, immunohistochemistry and ELISA were used to detect the expression of anabolic and catabolic gene expression. Alcian blue/Safranin O staining and GAG assay were used to measure cartilage matrix production. Cell proliferation and apoptosis were assessed by EdU staining and TUNEL assay, respectively. The results showed that hypoxia enhanced matrix production in both MHC and MDC and this effect was stronger on MDC. Under normoxia, MHC showed higher expression of cartilage markers and lower catabolic genes expression than MDC. Interestingly, hypoxia diminished the difference between MHC and MDC. IL1β potently induced MMPs expression regardless of cell population and oxygen tension. The fold induction of these MMPs in hypoxia was however much higher than in normoxia. In addition, hypoxia promoted the expression of HIF1α and HIF2α in MHC, while it only enhanced HIF1α expression but decreased the HIF2α expression in MDC. We concluded that hypoxia stimulated the redifferentiation of cultured chondrocytes, particularly in MDC derived from macroscopically diseased cartilage. Oxygen tension may profoundly and differentially influence inflammation‐associated cartilage injury and diseases by regulating the expression of HIF1α and HIF2α. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 9999:XX–XX, 2018. Abstract : Articular cartilage is relatively hypoxic. We found that hypoxia enhanced matrix production in both macroscopically healthy looking areas chondrocytes (MHC) and macroscopically damaged regions chondrocytes (MDC) and this effect was stronger on MDC. Under normoxia, MHC showed higher expression of cartilage markers and lower catabolic genes expression than MDC. While hypoxia diminished the difference between MHC and MDC. IL1β potently induced MMPs expression. The fold induction of these MMPs in hypoxia was however much higher than in normoxia.